Twelfth Five Year Plan (2012-2017) Faster, More Inclusive and Sustainable Growth Volume I - Planning Commission, Government of India (Planning Commission, Government of India, 2012)
India’s 1.25 billion citizens have higher expectations about their future today, than they have ever had before. They have seen the economy grow much faster in the past 10 years than it did earlier, and deliver visible benefits to a large number of people. This has understandably raised the expectations of all sections, especially those who have benefited less. Our people are now much more aware of what is possible, and they will settle for no less. The Twelfth Five Year Plan must rise to the challenge of meeting these high expectations.
Planning Commission Government of India
Planning Commission Government of India
Keywords: Twelfth Five Year Plan- Faster, More Inclusive and Sustainable Growth; Economic development in India